EXPLORING THE INFLATIONARY AND ECONOMIC EFFECT OF THE ABSENCE OF COINS IN TRADE (PMS) TRANSACTIONS IN NIGERIA: A DATA-DRIVEN APPROACH (FUDMA JOURNAL OF SCIENCES, 2024)
Coins are still widely used in financial transactions in various countries, including Nigeria, despite their economic importance. However, in Nigeria, people often do not realize how their attitudes and tastes toward coins' rejection contribute to inflation. This study employed the ARIMA model, the autoregressive (VAR) model, and the random forest machine learning method to analyze the impact of differentials from pump premium motor spirit (PMS) price changes on economic uncertainty and the inflation rate. The ARIMA model forecast showed that the absence of coins increases inflation for ahead periods. The impulse response from the VAR model shows a significant positive effect of the variables that can cause a significant response from the economic policy uncertainty, though with a zero value at the end period. The forecast variance error decomposition of the VAR model shows that the NPP variable, SPP variable, and ZPP variable increasingly contributed to the variations of economic uncertainty, more specifically in the long term. The machine learning method revealed that the ZPP and NPP variables have more importance and contribution in estimating economic uncertainty among study variables in Nigeria, with a small contribution from the SPP variable using the random forest method. The mean square error and node impurity increased the most when the ZPP variable was randomly permuted. The study emphasizes the adverse effect of coins' rejection or absence in the economy and argues that a coin's return can have a significant positive impact on the Nigerian economy by reducing inflation and facilitating financial inclusion.
Keywords: MAX Model; VAR Model; Random Forest; Coins; Nigeria